Population Structure and Genetic Diversity of Nile Tilapia (Oreochromis niloticus) Strains Cultured in Tanzania - Kajungiro, Redempta A.; Palaiokostas, Christos; Pinto, Fernando A. Lopes; Mmochi, Aviti J.; Mtolera, Marten; Houston, Ross D.; de Koning, Dirk Jan (Frontiers in Genetics, 2019)
Understanding population structure and genetic diversity within and between local Nile tilapia lines cultured in Tanzania is important for sustainable aquaculture. This study investigated the genetic structure and diversity amongst seven Nile tilapia populations in Tanzania (Karanga, Igunga, Ruhila, Fisheries Education and Training Agency, Tanzania Fisheries Research Institute, Kunduchi, and Lake Victoria). Double- digest restriction site-associated DNA (ddRAD) libraries were prepared from 140 individual fish (20 per population) and sequenced using an Illumina HiSeq 4000 resulting in the identification of 2,180 informative single nucleotide polymorphisms (SNPs). Pairwise Fst values revealed strong genetic differentiation between the closely related populations; FETA, Lake Victoria, and Igunga and those from TAFIRI and Karanga with values ranging between 0.45 – 0.55. Population structure was further evaluated using Bayesian model-based clustering (STRUCTURE) and discriminant analysis of principal components (DAPC). Admixture was detected amongst Karanga, Kunduchi and Ruhila populations. A cross-validation approach (25 % of individual fish from each population was considered of unknown origin) was conducted in order to test the efficiency of the SNP markers to correctly assign individual fish to the population of origin. The cross-validation procedure was repeated 10 times resulting in 77 % of the tested individual fish being allocated to the correct population. Overall our results provide a new database of informative SNP markers for both conservation management and aquaculture activities of Nile tilapia strains in Tanzania.